ANALISIS MAKNA KONOTATIF LIRIK LAGU DALAM ALBUM “BEST SELECTION BLANC” OLEH AIMER - Essy Cahyani; Hendri Zalman (Universitas Negeri Padang, 2021)
AbstrakThis research is motivated by the difficulty of understanding the connotative meaning contained in a sentence so that it can lead to misunderstandings in interpreting the meaning that the speaker wants to convey. The objectives of this study were to: (1) describe the connotative meanings contained in the song lyrics in album Best Selection “Blanc” by Aimer, (2) describe the types of connotative meanings used in the song lyrics in the album Best Selection